2008
DOI: 10.1111/j.1744-7909.2008.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide Characterization of Long Terminal Repeat ‐retrotransposons in Apple Reveals the Differences in Heterogeneity and Copy Number between Ty1‐copiaand Ty3‐gypsyRetrotransposons

Abstract: The conserved domains of reverse transcriptase (RT) genes of Ty1-copia and Ty3-gypsy groups of long terminal repeat (LTR) retrotransposons were isolated from the Malus domestica genome using degenerate oligonucleotide primers. Sequence analysis showed that 45% of Ty1-copia and 63% of Ty3-gypsy RT sequences contained premature stop codons and/or indels disrupting the reading frame. High heterogeneity among RT sequences of both Ty1-copia and Ty3-gypsy group retrotransposons was observed, but Ty3-gypsy group retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
1
15
0
1
Order By: Relevance
“…Although a number of LTR retrotransposons have been isolated in apple, most of them are RT fragments (Tignon et al 2001;Sun et al 2008), and only five complete retrotransposons have been submitted to the GenBank database (Yao et al 2001;Antonius-Klemola et al 2006;Han et al 2007). No example of a complete Ty1-copia retrotransposon is available in the literature for apple.…”
Section: Introductionmentioning
confidence: 97%
“…Although a number of LTR retrotransposons have been isolated in apple, most of them are RT fragments (Tignon et al 2001;Sun et al 2008), and only five complete retrotransposons have been submitted to the GenBank database (Yao et al 2001;Antonius-Klemola et al 2006;Han et al 2007). No example of a complete Ty1-copia retrotransposon is available in the literature for apple.…”
Section: Introductionmentioning
confidence: 97%
“…There are four possible explanations for this. First, the retroelement "copy-and-paste" mechanism is errorprone, owning to the low fidelity and lack of proofreading activity in the rt gene, which leads to sequence diversity (Sun et al, 2008). Second, according to Kumar and Bennetzen (1999), retroelement heterogeneity could gradually be maintained over generations, through vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Ty3-gypsy elements have also been reported to be present in high copy number in several plant genomes, in Vicia species Ty3-gypsy elements contribute 18% to 35% of their genome 20 and in apple genome Ty3-gypsy contributes 33.5%. 18 In this study, it was found that, LTR retrotransposons constitute about 19% of jute genome having approximately 31,000 copies of Ty1-gypsy elements and 3,600 copies of Ty3-gypsy elements. This might be an indication of the importance of Ty1-copia retrotransposons in jute genome evolution and its large Figure 5A (See previous page).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard we relied on the approach followed out by other groups. 1,18 LTR retrotransposons copy number in jute. To determine the copy numbers of Ty1-copia and Ty3-gypsy elements of jute genome two heterogenous populations of 280 bp Ty1-copia and 290 bp Ty3-gypsy whole PCR products were used as probes for of the reverse transcriptase, 31 (2) mixture of active and defective populations of retrotransposons, 2 (3) pressure of copy number since the divergence of a retrotransposon in any population is proportional to their copy number, 22,32 (4) homologous recombination, 33,34 (5) horizontal and (6) vertical transmission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation